Corticosteroid Phobia: A Key Barrier to Treatment in Young Women with Idiopathic Granulomatous Mastitis - Lin W; Wang Q; Liu J; Tan Q (International Journal of Women's Health)
Weiyi Lin,1,2,* Qiuzhou Wang,2,* Jia Liu,1,2 Qiuwen Tan1,2 1Division of Breast Surgery, Department of General Surgery, West China Hospital, Sichuan University, Chengdu City, Sichuan Province, People’s Republic of China; 2Breast Center, West China Hospital, Sichuan University, Chengdu City, Sichuan Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiuwen Tan, Division of Breast Surgery, Department of General Surgery, West China Hospital, Sichuan University, No. 37 Guo Xue Alley, Chengdu City, Sichuan Province, 610041, People’s Republic of China, Email hxtanqiuwen@163.comPurpose: Corticosteroids are recommended as a first-line treatment for idiopathic granulomatous mastitis (IGM), a disease that usually occurs in young women. Corticosteroid phobia is a fear of corticosteroids and one of the main reasons for poor treatment compliance. Despite the increasing recognition of corticosteroid phobia, there has been a lack of studies on this issue in IGM. This study was designed to investigate the prevalence and degree of corticosteroid phobia in IGM patients.Patients and Methods: A cross-sectional survey was conducted among IGM patients who were receiving treatment at West China Hospital between June 2023 and December 2023. A modified version of Topical Corticosteroid Phobia Scale (TOPICOP) was used to assess the prevalence and degree of corticosteroid phobia in patients with IGM. Sources of drug information were also identified. Scores were expressed as mean ± standard deviation. Independent t-test was used to compare the TOPICOP item scores between different categorical variables.Results: A total of 50 IGM patients were included in the present study. The median global TOPICOP score was 61.29 ± 11.71%. About 80% of patients represented with severe phobia, which their global TOPICOP score was above 50.0%. About 50% of participants showed fear of adverse effect of oral corticosteroids. About 89.6% of participants who received corticosteroid treatment showed their well to adhere to the doctor’s advice. IGM patients with systemic symptoms were associated with higher scores in the behavior domain and/or global TOPICOP. Young, low educated, and unemployed individuals were more likely to have corticosteroid phobia (p < 0.05). There was no difference in the scores based on skin redness, abscess formation, ulcer or fistula, initial treatment choice, or monthly household income. Medical professionals were the primary sources of information about corticosteroid.Conclusion: Corticosteroid phobia was highly prevalent among the women with IGM, as well as the high treatment adherence. Women showed a high preference for non-corticosteroid therapies as alternative therapies. Providing more comprehensive and professional knowledge by physicians might be an effective method to attenuate corticosteroid phobia.Keywords: corticosteroid phobia, treatment adherence, idiopathic granulomatous mastitis, breast